Digenic Inheritance in Juvenile Open-Angle Glaucoma - Somarajan, Bindu I.; Gupta, Shikha; Mahalingam, Karthikeyan; Azmira, Kishan; Gupta, Viney (Journal of Pediatric Genetics, 2021)
Juvenile open-angle glaucoma (JOAG) is an uncommon subset of primary glaucoma with an onset before the age of 40 years. In this case report, we describe the cosegregation of MYOC, p.Pro370Leu and LTBP2, p.Pro432Leu mutations in a family with JOAG. The family with autosomal dominant JOAG belonged to Northern India. The samples of proband and her parents were evaluated by whole exome sequencing. Sanger sequencing was conducted in all the study participants to check the mutations identified. Both MYOC and LTBP2 mutations were found to cosegregate in affected individuals leading to a severe JOAG phenotype, thereby suggesting a digenic inheritance of MYOC with LTBP2 in this family.
Keywords: glaucoma; digenic; inheritance; mutation; phenotype